A Measure of the Depth of Housing Stress and its Application in Australia. Issue 1 (12th March 2013) - Tanton, Robert; Phillips, Ben
<x xml:space="preserve">Abstract</x> One calculation used in Australia for housing stress is that a household spends more than 30 per cent of their income on housing costs and they are in the bottom two quintiles of the income distribution. One problem with this measure is that a household is either in housing stress, or not in housing stress. This article extends work by Chaplin and Freeman on the depth of housing stress to include a 30/40 measure. This article also explores how different groups of households have different levels of housing stress, and different depths of housing stress, and why these may diverge. Depth of housing stress is compared by age group; housing tenure and over time. Finally, conclusions and implications for Government policy are suggested.